Theory of mind and literature - Leverage, Paula, 1970- (Book collections on Project MUSE., 2011)
Theory of Mind is what enables us to?put ourselves in another?s shoes.? It is mindreading, empathy, creative imagination of another?s perspective: in short, it is simultaneously a highly sophisticated ability and a very basic necessity for human communication. Theory of Mind is central to such commercial endeavors as market research and product development, but it is also just as important in maintaining human relations over a cup of coffee. Not surprisingly, it is a critical tool in reading and understanding literature, which abounds with characters, situations, and?other people?s shoes.? Furthermore, it is becoming increasingly apparent that reading literature also hones these critical mindreading skills. Theory of Mind and Literature is a collection of nineteen essays by prominent scholars (linguists, cognitive scientists, and philosophers) working in the cutting-edge field of cognitive literary studies, which explores how we use Theory of Mind in reading and understanding literature.